Effect of abscisic acid on symbiotic nitrogen fixation activity in the root nodules of Lotus japonicus - Tominaga, Akiyoshi (Landes Bioscience, 2010)
The phytohormone abscisic acid (ABA) is known to be a negative regulator of legume root nodule formation. By screening Lotus japonicus seedlings for survival on an agar medium containing 70 µM ABA, we obtained mutants that not only showed increased root nodule number, but also enhanced nitrogen fixation. The mutant was designated enf1 (enhanced nitrogen fixation 1) and was confirmed to be monogenic and incompletely dominant. In long-term growth experiments with M. loti, although some yield parameters were the same for both enf1 and wild-type plants, both the dry weight and N content of 100 seeds and entire enf1 plants were significantly larger compared than those traits in wild-type seeds and plants. The augmentation of the weight and N content of the enf1 plants most likely reflects the increased N supplied by the additional enf1 nodules and the concomitant increase in N fixation activity. We determined that the endogenous ABA concentration and the sensitivity to ABA of enf1 were lower than that of wild-type seedlings. When wild-type plants were treated with abamine, a specific inhibitor of 9-cis-epoxycarotenoid dioxygenase (NCED), which results in reduced ABA content, the N fixation activity of abamine-treated plants was elevated to the same levels as enf1. We also determined that production of nitric oxide (NO) in enf1 nodules was decreased. We conclude that endogenous ABA concentration not only regulates nodulation, but also nitrogen fixation activity by decreasing NO production in nodules.